Aqueous two-phase systems: a simple methodology to obtain mixtures enriched in main toxins of Bothrops alternatus venom - Gómez, Gabriela Noemí (2016)
Fil: Gómez, Gabriela Noemí. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas Naturales y Agrimensura; Argentina.